Women’s Iconography in Colombian Textbooks (2018)
This work aims to observe the relationship between the achievements of Colombian women in gender equality and their iconographic representation in the illustrations of Spanish Language textbooks for primary and secondary school. The research question was as follows: What treatment is given to women in the illustrations of Spanish Language textbooks for primary and secondary school in relation to gender equality? The methodology is based on the iconographic analysis method proposed by Ramírez (2001).